2021
DOI: 10.3389/fpsyg.2021.644323
|View full text |Cite
|
Sign up to set email alerts
|

The Moderation Effects of Comparative Thinking Between Gratitude and Negative Affect During the COVID-19 Outbreak

Abstract: The aim of this research was to examine the moderation effects of comparative thinking (CT) across the relationship between gratitude and affect during the COVID-19 outbreak. To this purpose, multiple regression as well as moderation analyses were carried out. Age and sex were also addressed as variables of interest as described in previous literature. A sample of 306 north Americans was recruited by crowdsourcing platform ProA to obtain a representative sample based on age and gender. The participants filled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Some individuals with CSBD may involve in upward counterfactual thinking (e.g., How much my life could have been better if I had not been harmed by others? ), which can increase negative emotions connected with holding grudges against perpetrators, in this way blocking the potential of gratitude for reducing negative emotions (see Bernabe-Valero et al, 2021 ). This topic needs further investigation, as it may be a fruitful avenue of exploration of the interactions between gratitude and forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals with CSBD may involve in upward counterfactual thinking (e.g., How much my life could have been better if I had not been harmed by others? ), which can increase negative emotions connected with holding grudges against perpetrators, in this way blocking the potential of gratitude for reducing negative emotions (see Bernabe-Valero et al, 2021 ). This topic needs further investigation, as it may be a fruitful avenue of exploration of the interactions between gratitude and forgiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that gratitude was significantly and negatively associated with depression, which was consistent with the findings of the pre-pandemic COVID-19 study ( 55 ). Gratitude plays an important role in post-traumatic growth, especially during the pandemic period, and gratitude has many physical and psychological benefits for individuals, which can lead to a decrease in depression ( 56 , 57 ). Therefore, activities to express gratitude can be actively pursued, which may help to cope with some of the psychological problems during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…For women, experiencing a crisis significantly reduced their purpose. Psychological therapies aimed at reinterpreting past difficult experiences and reclaiming purposes in life can reduce the negative psychological effects of the pandemic [4]. Counterfactual thinking, which can mitigate stressful or traumatic experiences, can be one such method [3,78].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The pandemic has caused severe stress for the general population worldwide [3]. Many studies have suggested that the current situation will have a significant psychological effect into the future [4,5]. The COVID-19 pandemic has exacerbated mental health issues [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation